2021
DOI: 10.1097/spv.0000000000000911
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Long-Term Use of Percutaneous Tibial Nerve Stimulation for Management of Overactive Bladder Syndrome

Abstract: Objectives The aims of the study were to estimate the rate of percutaneous tibial nerve stimulation maintenance therapy (PTNS-MT) among women with overactive bladder syndrome (OAB) and evaluate factors associated with long-term use of PTNS. Methods Patients who completed 12 weekly sessions of PTNS (PTNS-IN) for OAB between 2009 and 2016 within the Kaiser Permanente Northern California were identified using Current Procedural Terminology and Internationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…46 A Northern California claims-based analysis of 1331 patients with a mean age of 69.8 years initiating PTNS for OAB found just 26% completed a 12-week initial course. 51 Interestingly, older age trended as a predictor of continuing therapy: patients completing maintenance were older (68.9 vs. 70.9 years, p = 0.11) and age >85 years trended as a positive predictor (OR 1.98, p = 0.10).…”
Section: Safety and Efficacy Data In Elderly Patientsmentioning
confidence: 92%
See 1 more Smart Citation
“…46 A Northern California claims-based analysis of 1331 patients with a mean age of 69.8 years initiating PTNS for OAB found just 26% completed a 12-week initial course. 51 Interestingly, older age trended as a predictor of continuing therapy: patients completing maintenance were older (68.9 vs. 70.9 years, p = 0.11) and age >85 years trended as a positive predictor (OR 1.98, p = 0.10).…”
Section: Safety and Efficacy Data In Elderly Patientsmentioning
confidence: 92%
“…A retrospective study in over 400 patients treated with PTNS for OAB found just 57% continue after 12‐week initial treatment, with 40% of those stopping maintenance therapy due to logistic reasons and physical strain 46 . A Northern California claims‐based analysis of 1331 patients with a mean age of 69.8 years initiating PTNS for OAB found just 26% completed a 12‐week initial course 51 . Interestingly, older age trended as a predictor of continuing therapy: patients completing maintenance were older (68.9 vs. 70.9 years, p = 0.11) and age >85 years trended as a positive predictor (OR 1.98, p = 0.10).…”
Section: Posterior Tibial Nerve Stimulationmentioning
confidence: 99%
“…In a prospective study that had high adherence to therapy sessions, UUI responder rates have been shown to be as high as 78% after 12 sessions[ 11 ]. However, the available data suggest that outside of prospective clinical studies, real-world therapy adherence to the first 12 sessions varies and may be as low as 26%[ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using the calculator in clinical practice could counsel women from minoritized racial groups away from Botox use. Studies have shown that women from historically marginalized racial groups are less likely to seek treatment for OAB and less likely to use third-line treatments for OAB 10,11 . The lower predicted success rate for patients who are not White may lead clinicians to recommend a different treatment option, a phenomenon that we have already seen in obstetrics with the use of race in the original vaginal birth after cesarean calculators 12 …”
mentioning
confidence: 99%
“…Studies have shown that women from historically marginalized racial groups are less likely to seek treatment for OAB and less likely to use third-line treatments for OAB. 10,11 The lower predicted success rate for patients who are not White may lead clinicians to recommend a different treatment option, a phenomenon that we have already seen in obstetrics with the use of race in the original vaginal birth after cesarean calculators. 12 Including race as a stand-alone variable in calculators assumes that race represents a well-defined variable such as age or education level, which is not the case.…”
mentioning
confidence: 99%